Sistem Pendukung Keputusan Penilaian Karyawan Pada Sekolah Triguna Utama Menggunakan Metode SMART (Simple Multi Attribute Rating Technique) - Ikhsan Aprijal; Niki Ratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Decision Support System is a system used to support and help improve the quality of employee work and employee creativity. Companies need an employee performance appraisal system by giving promotions if there are vacant positions to employees who excel. The assessment of the selection of exemplary employees given is still subjective, that is, there are no parameters in the assessment and the process of making it and the information obtained is still slow. It is feared that this will lead to confusion and inaccuracy in the selection of exemplary employees so that they are not right on target. This problem can be corrected by building a decision support system for selecting exemplary employees using the SMART (Simple Multi Attribute Rating Technique) method. Implementation of a Web-based Decision Making System for employee achievements makes it easier for employees to process absences or record employee attendance at Triguna Utama School.